1993
DOI: 10.1364/ao.32.006399
|View full text |Cite
|
Sign up to set email alerts
|

Optical-fiber strain sensors with asymmetric etched structures

Abstract: Optical-fiber strain gauges with asymmetric etched structures have been analyzed, fabricated, and tested. These sensors are very sensitive with a gauge factor as high as 170 and a flat frequency response to at least 2.7 kHz. The gauge factor depends on the asymmetry of the etched structures and the number of etched sections. To understand the physical principles involved, researchers have used structural analysis programs based on a finite-element method to analyze fibers with asymmetric etched structures unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…5,6 Such stretchinduced microbends effectively enhance refractive index modulation in the CO 2 -laser-carved LPFGs, which is similar to the case of the microbend-induced LPFG. 5 Therefore, the refractive index modulation efficiency in the CO 2 -laser-carved LPFG is higher than that of the CO 2 -laser-induced LPFG without periodic grooves.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…5,6 Such stretchinduced microbends effectively enhance refractive index modulation in the CO 2 -laser-carved LPFGs, which is similar to the case of the microbend-induced LPFG. 5 Therefore, the refractive index modulation efficiency in the CO 2 -laser-carved LPFG is higher than that of the CO 2 -laser-induced LPFG without periodic grooves.…”
mentioning
confidence: 56%
“…6 So periodic microbends will be observed when a CO 2 -laser-carved LPFG with asymmetric grooves is stretched, as shown in Fig. 6.…”
mentioning
confidence: 97%
“…The research by Vaziri et al [12] showed a good linearity for the coefficient of strain increased with an increase in the depth of grooves. Experiments in this paper showed the dissimilar conclusion that the absolute value of sensitivity may comply with the linearity for the depth of grooves, not the original sensitivity.…”
Section: Resultsmentioning
confidence: 92%
“…4, small lateral bends, i.e. periodic microbends, will be induced, resulting from the asymmetric structure, at each grooved section while the CO 2 -laser-induced LPFG with asymmetric grooves is stretched longitudinally [14,15]. As a result, additional refractive index perturbation is induced by the stretch-induced microbend in the grating due to the photoelastic effect, thus enhancing refractive index modulation in the CO 2 -laser-induced LPFG, which is similar to the case of the microbend-induced LPFG [16][17][18].…”
Section: Applying Tensile Strainmentioning
confidence: 99%